Transformasi Dakwah Di Era Digital: Analisis Model Dakwah Felix Siauw Pada Podcast Escape - Nur Halimah; Muhammad Yusuf (IAIN Padangsidimpuan, 2026)
This study explores the phenomenon of Islamic preaching (da'wah) transformation in the digital age, focusing on Felix Siauw's communication strategy during his appearance on the Escape Podcast on Raymond Chin’s YouTube channel. The transition from conventional media to digital platforms represents more than a simple change of medium; it signifies a paradigm shift in how religious messages are produced, distributed, and consumed. In this modern ecosystem, preachers are required to adapt to contemporary audiences who prioritize content that is interactive, relevant, and accessible at any time. Utilizing a qualitative content analysis approach within a case study design, this research applies Richard M. Perloff’s Persuasion Theory, examining both central and peripheral routes. The analysis focuses on rhetorical patterns, messaging strategies, and the dynamics of preaching interaction within the podcast format. The findings reveal that Felix Siauw successfully maintains the effectiveness of his message amidst intense digital competition through dialogic narrative communication. This success is further bolstered by enhanced personal credibility and the implementation of persuasive strategies that align with the fluid logic of digital media. Ultimately, this study provides a significant contribution to contemporary Islamic communication research, particularly in mapping how preaching practices evolve to remain relevant and influential within an ever-changing and dynamic digital ecosystem